# 18. The Natural Numbers and Induction in Lean¶

## 18.1. Induction and Recursion in Lean¶

Internally, in Lean, the natural numbers are defined as a type generated inductively from an axiomatically declared zero and succ operation:

inductive nat : Type
| zero : nat
| succ : nat → nat


If you click the button that copies this text into the editor in the online version of this textbook, you will see that we wrap it with the phrases namespace hidden and end hidden. This puts the definition into a new “namespace,” so that the identifiers that are defined are hidden.nat, hidden.nat.zero and hidden.nat.succ, to avoid conflicting with the one that is in the Lean library. Below, we will do that in a number of places where our examples duplicate objects defined in the library. The unicode symbol ℕ, entered with \N or \nat, is a synonym for nat.

Declaring nat as an inductively defined type means that we can define functions by recursion, and prove theorems by induction. For example, these are the first two recursive definitions presented in the last chapter:

open nat

def two_pow : ℕ → ℕ
| 0        := 1
| (succ n) := 2 * two_pow n

def fact : ℕ → ℕ
| 0        := 1
| (succ n) := (succ n) * fact n


Addition and numerals are defined in such a way that Lean recognizes succ n and n + 1 as essentially the same, so we could instead write these definitions as follows:

def two_pow : ℕ → ℕ
| 0       := 1
| (n + 1) := 2 * two_pow n

def fact : ℕ → ℕ
| 0       := 1
| (n + 1) := (n + 1) * fact n


If we wanted to define the function m^n, we would do that by fixing m, and writing doing the recursion on the second argument:

def pow : ℕ → ℕ → ℕ
| m 0        := 1
| m (n + 1)  := m * pow m n


In fact, this is how the power function on the natural numbers, nat.pow, is defined in Lean’s library.

Lean is also smart enough to interpret more complicated forms of recursion, like this one:

def fib : ℕ → ℕ
| 0        := 0
| 1        := 1
| (n + 2)  := fib (n + 1) + fib n


In addition to defining functions by recursion, we can prove theorems by induction. In Lean, each clause of a recursive definition results in a new identity. For example, the two clauses in the definition of pow above give rise to the following two theorems:

import data.nat.pow
open nat

example (n : ℕ) : pow n 0 = 1 := rfl
example (m n : ℕ) : pow m (n+1) = m * pow m n := rfl


Lean defines the usual notation for exponentiation:

import data.nat.pow
open nat

example (n : ℕ) : n^0 = 1 := rfl
example (m n : ℕ) : m^(n+1) = m * m^n := rfl

#check @pow_zero
#check @pow_succ


Notice that we could alternatively have used pow m n * n in the second clause of the definition of pow. Of course, we can prove that the two definitions are equivalent using the commutativity of multiplication, but, using a proof by induction, we can also prove it using only the associativity of multiplication, and the properties 1 * m = m and m * 1 = m. This is useful, because the power function is also often used in situations where multiplication is not commutative, such as with matrix multiplication. The theorem can be proved in Lean as follows:

import data.nat.pow
open nat

example (m n : ℕ) : m^(succ n) = m^n * m :=
nat.rec_on n
(show m^(succ 0) = m^0 * m, from calc
m^(succ 0) = m * m^0 : by rw pow_succ
... = m * 1   : by rw pow_zero
... = m       : by rw mul_one
... = 1 * m   : by rw one_mul
... = m^0 * m : by rw pow_zero)
(assume n,
assume ih : m^(succ n) = m^n * m,
show m^(succ (succ n)) = m^(succ n) * m, from calc
m^(succ (succ n)) = m * m^(succ n)   : by rw pow_succ
... = m * (m^n * m)    : by rw ih
... = (m * m^n) * m    : by rw mul_assoc
... = m^(succ n) *m    : by rw pow_succ)


This is a typical proof by induction in Lean. It begins with the phrase nat.rec_on n, and is followed by the base case and the inductive hypothesis. (The phrase open nat allows us to write pow instead of nat.pow. This theorem is called pow_succ' in the library.The proof can be shortened using rewrite:

import data.nat.pow
open nat

example (m n : ℕ) : m^(succ n) = m^n * m :=
nat.rec_on n
(show m^(succ 0) = m^0 * m, by
rw [pow_succ, pow_zero, mul_one, one_mul])
(assume n,
assume ih : m^(succ n) = m^n * m,
show m^(succ (succ n)) = m^(succ n) * m,
by rw [pow_succ, pow_succ, mul_assoc, ←ih, ←pow_succ])


Remember that you can write a rewrite proof incrementally, checking the error messages to make sure things are working so far, and to see how far Lean got.

As another example of a proof by induction, here is a proof of the identity m^(n + k) = m^n * m^k.

import data.nat.pow
open nat

example (m n k : ℕ) : m^(n + k) = m^n * m^k :=
nat.rec_on k
(show m^(n + 0) = m^n * m^0, from calc
m^(n + 0) = m^n       : by rw add_zero
... = m^n * 1   : by rw mul_one
... = m^n * m^0 : by rw pow_zero)
(assume k,
assume ih : m^(n + k) = m^n * m^k,
show m^(n + succ k) = m^n * m^(succ k), from calc
m^(n + succ k) = m^(succ (n + k)) : by rw nat.add_succ
... = m^(n + k) * m    : by rw pow_succ'
... = m^n * m^k * m    : by rw ih
... = m^n * (m^k * m)  : by rw mul_assoc
... = m^n * m^(succ k) : by rw pow_succ')


Notice the same pattern. This time, we do induction on k, and the base case and inductive step are routine. The theorem is called pow_add in the library, and once again, with a bit of cleverness, we can shorten the proof with rewrite:

import data.nat.pow
open nat

example (m n k : ℕ) : m^(n + k) = m^n * m^k :=
nat.rec_on k
(show m^(n + 0) = m^n * m^0,
(assume k,
assume ih : m^(n + k) = m^n * m^k,
show m^(n + succ k) = m^n * m^(succ k),
by rw [nat.add_succ, pow_succ', ih, mul_assoc, pow_succ'])


You should not hesitate to use calc, however, to make the proofs more explicit. Remember that you can also use calc and rewrite together, using calc to structure the calculational proof, and using rewrite to fill in each justification step.

## 18.2. Defining the Arithmetic Operations in Lean¶

In fact, addition and multiplication are defined in Lean essentially as described in Section 17.4. The defining equations for addition hold by reflexivity, but they are also named add_zero and add_succ:

import data.nat.basic
open nat

variables m n : ℕ

example : m + 0 = m := add_zero m
example : m + succ n = succ (m + n) := add_succ m n


Similarly, we have the defining equations for the predecessor function and multiplication:

import data.nat.basic
open nat

#check @pred_zero
#check @pred_succ
#check @mul_zero
#check @mul_succ


Here are the five propositions proved in Section 17.4.

theorem succ_pred (n : ℕ) : n ≠ 0 → succ (pred n) = n :=
nat.rec_on n
(assume H : 0 ≠ 0,
show succ (pred 0) = 0, from absurd rfl H)
(assume n,
assume ih,
assume H : succ n ≠ 0,
show succ (pred (succ n)) = succ n,
by rewrite pred_succ)

theorem zero_add (n : nat) : 0 + n = n :=
nat.rec_on n
(show 0 + 0 = 0, from rfl)
(assume n,
assume ih : 0 + n = n,
show 0 + succ n = succ n, from
calc
0 + succ n = succ (0 + n) : rfl
... = succ n : by rw ih)

theorem succ_add (m n : nat) : succ m + n = succ (m + n) :=
nat.rec_on n
(show succ m + 0 = succ (m + 0), from rfl)
(assume n,
assume ih : succ m + n = succ (m + n),
show succ m + succ n = succ (m + succ n), from
calc
succ m + succ n = succ (succ m + n) : rfl
... = succ (succ (m + n)) : by rw ih
... = succ (m + succ n) : rfl)

theorem add_assoc (m n k : nat) : m + n + k = m + (n + k) :=
nat.rec_on k
(show m + n + 0 = m + (n + 0), by rw [add_zero, add_zero])
(assume k,
assume ih : m + n + k = m + (n + k),
show m + n + succ k = m + (n + (succ k)), from calc
m + n + succ k = succ (m + n + k)   : by rw add_succ
... = succ (m + (n + k)) : by rw ih
... = m + succ (n + k)   : by rw ←add_succ
... = m + (n + succ k)   : by rw ←add_succ)

theorem add_comm (m n : nat) : m + n = n + m :=
nat.rec_on n
(show m + 0 = 0 + m, by rewrite [add_zero, zero_add])
(assume n,
assume ih : m + n = n + m,
show m + succ n = succ n + m, from calc
m + succ n = succ (m + n) : by rw add_succ
... = succ (n + m) : by rw ih
... = succ n + m   : by rw succ_add)


## 18.3. Exercises¶

1. Formalize as many of the identities from Section 17.4 as you can by replacing each sorry with a proof.

import data.nat.basic
open nat

--1.a.
example : ∀ m n k : nat, m * (n + k) = m * n + m * k := sorry

--1.b.
example : ∀ n : nat, 0 * n = 0 := sorry

--1.c.
example : ∀ n : nat, 1 * n = n := sorry

--1.d.
example : ∀ m n k : nat, (m * n) * k = m * (n * k) := sorry

--1.e.
example : ∀ m n : nat, m * n= n * m := sorry

2. Formalize as many of the identities from Section 17.5 as you can by replacing each sorry with a proof.

import data.nat.basic
open nat

--2.a.
example : ∀ m n k : nat, n ≤ m → n + k ≤ m  + k := sorry

--2.b.
example : ∀ m n k : nat, n + k ≤ m + k → n ≤ m := sorry

--2.c.
example : ∀ m n k : nat, n ≤ m → n * k ≤ m * k := sorry

--2.d.
example : ∀ m n : nat, m ≥ n → m = n ∨ m ≥ n+1 := sorry

--2.e.
example : ∀ n : nat, 0 ≤ n := sorry